2019
DOI: 10.1186/s13048-019-0577-2
|View full text |Cite
|
Sign up to set email alerts
|

Organoids of epithelial ovarian cancer as an emerging preclinical in vitro tool: a review

Abstract: Epithelial ovarian cancer (EOC) remains the most lethal gynecological cancer in developed countries, indicating the need for further research. Although current cancer models prove useful, they have major limitations. Organoids, a novel in vitro 3D cell culture technique, derived from stem cells, could provide a bridge between the current preclinical platforms. However, this technique is still in its early stages. After conducting a systematic literature search, only sixteen manuscripts concerning ovarian relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Different 3D cell culture models have been applied to study EOC dissemination and response to therapy (recently reviewed in [39,54,55]), including the application of microfluidic technologies based on 3D spheroidbased sampling [54,56]. Since the fallopian tubes have been recently recognized as a potential primary origin of HGSOC [57], organoid cultures have been also produced from human and mouse fallopian tube epithelium [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different 3D cell culture models have been applied to study EOC dissemination and response to therapy (recently reviewed in [39,54,55]), including the application of microfluidic technologies based on 3D spheroidbased sampling [54,56]. Since the fallopian tubes have been recently recognized as a potential primary origin of HGSOC [57], organoid cultures have been also produced from human and mouse fallopian tube epithelium [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36]. Indeed, we and others have shown that 3D cultures display altered/reduced sensitivities to chemotherapeutic agents compared to 2D models, which may have a significant impact on the success of drug testing pipelines for cancer [36], including EOC [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Tumoroids permit a faster culturing method, amenable to multiplexing a wider range of analysis tools in a pre-clinical setting. Several studies have shown promising results of tumoroid cultures mimicking histological morphology and drug responses across multiple cancer types [11][12][13][14][15]. However, a thorough analysis of the shifting stromal cell populations and the resulting effects on cancer cell behavior as a product of the culturing method have yet to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, several recent publications point that the in vitro cancer barrier is being transposed with the reconstruction of diversified tissue tumors on a plate, such as mammary gland, lungs, ovaries, and several others. [108][109][110][111][112]…”
Section: Cancerous Cellsmentioning
confidence: 99%